CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Verify the following:
(a) $$18\times [7+(-3)]=[18\times 7]+[18\times (-3)]$$
(b) $$(-21)\times [(-4)+(-6)]=[(-21)\times (-4)]+[(-21)\times (-6)]$$


Solution

(a) LHS $$=18\times \left[ 7+\left( -3 \right)  \right] =18\times 4=72$$
     RHS $$=\left[ 18\times 7 \right] +\left[ 18\times \left( -3 \right)  \right] $$ $$=126+\left( -54 \right) =72$$   (verified)

(b) LHS $$=\left( -21 \right) \times \left[ \left( -4 \right) +\left( -6 \right)  \right] =\left( -21 \right) \times \left( -10 \right) =210$$
     RHS $$=\left[ \left( -21 \right) \times \left( -4 \right)  \right] +\left[ \left( -21 \right) \times \left( -6 \right)  \right] =84+126=210$$    (verified)

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image